MALAYSIAN CHEMISTRY TEACHERS’ CHALLENGES TO PRACTICE DIFFERENTIATED INSTRUCTION IN CLASSROOM - Muhamad Furkan Mat Salleh; Rose Amnah Abd. Rauf; Rohaida Mohd Saat (MOJES: Malaysian Online Journal of Educational Sciences, 2022)
Regardless of students’ differences, they should have opportunities to learn in a classroom environment that adequately promotes their interests and scaffolds their progress. Often, research highlights the struggles teachers face in accommodating learners’ needs while ensuring effective lesson delivery at various educational levels. Although there have been a growing number of studies investigating the use of differentiated instruction in chemistry, there is a scarcity of research focusing on challenges to practice differentiated instruction in chemistry classrooms, especially in the Malaysian context. This study explored chemistry teachers’ challenges to practice differentiated instruction in their classrooms. The researchers elicited sixteen chemistry teachers’ experiences selected through purposive sampling in one-to-one semi-structured interviews. Thematic analysis of the data revealed four major challenges that the teachers face: catering to students’ needs, lesson planning and delivery, support and skill and time constraints in practising differentiation. Furthermore, it was found that teachers face more challenges on governable factors that could be rectified to help teachers successfully implement differentiated instruction. Finally, the study suggested that chemistry teachers involve in professional development training to enhance their knowledge and skills in differentiated instruction.